CTIM-09. ENRICHED TCR/BCR VDJ REARRANGEMENTS CORRELATE WITH MRI AND SURVIVAL OUTCOMES IN PATIENTS WITH RECURRENT HIGH-GRADE GLIOMA TREATED WITH CAN-3110. (14th November 2022) - Antonio Chiocca, E; Nakashima, Hiroshi; Mo, Xiaokui; Solomon, Isaac; Ling, Alexander; Woods, Jared; Bernstock, Joshua; Villa, Genaro; Piranlioglu, Raziye; Landivar, Ana Montalvo; Masud, Nafisa; Triggs, Daniel; et al.
Abstract: BACKGROUND: CAN-3110 (rQNestin34.5v2) is an HSV-1 oncolytic viral immunotherapy with one copy of the inflammatory ICP34.5 gene under transcriptional control of the Nestin glioma-specific promoter. We completed a phase 1 sequential dose-escalation trial of CAN-3110 in recurrent high-grade glioma (rHGG). METHODS: CAN-3110 was injected intratumorally starting at 1x10 6 plaque forming units (pfu) and dose- escalated by half log up to 1x10 10 pfu in biopsy confirmed rHGG. An expansion cohort of 12 patients was then accrued at 1x10 9 pfus. Blood and post-injection rHGG were collected. RESULTS: 41 rHGG patients were treated (42 separate interventions): median age 56 years (range 27-74); 21 females, 20 males; median baseline KPS 90 (range 70-100). CAN-3110 administration was well-tolerated with no dose limiting toxicities. Median overall survival (mOS) was 11.9 months. Histologic and molecular analyses showed significantly increased T cell infiltration in post treatment samples with elevated T cell and/or B cell receptor (TCR/BCR) transcripts which correlated with patient survival (HR 0.26 for patients with elevated TCR/BCR rearrangements as compared to patients with low). Volumetric analyses of MRI suggest a trend between reduction in the relative change in tumor growth, TCR/BCRs enrichment and survival in CAN-3110 treated patients. CLINICAL IMPLICATIONS: Administration of CAN-3110 into rHGG was well tolerated. OS of CAN-3110 treated subjects compare favorably to historical controls. The association of increased TCR/BCR transcripts with survival suggests that CAN-3110 induces T cell responses against rHGG, supporting further clinical development of CAN-3110 viral immunotherapy.